MRI in Stress Urinary Incontinence: Endovaginal MRI With an Intracavitary Coil and Dynamic Pelvic MRI - Tasali, Nuri; Cubuk, Rahmi; Sinanoglu, Orhun; Sahin, Kemal; Saydam, Bulent (Urology Journal, 2012)
Purpose: To evaluate both morphology of the urethra and its supporting structures using endovaginal magnetic resonance imaging (EV-MRI) and the grade of the bladder neck prolapsus using dynamic pelvic MRI (DP-MRI) in women with stress urinary incontinence (SUI). Materials and Methods: We compared 25 women with SUI and 8 controls according to the different layers of the urethra, the degree of distortion in the periurethral, paraurethral, and pubourethral ligaments, the vesicourethral angle, the retropubic space, and the thickness of the puborectal muscle. The SUI group was also evaluated according to the number of deliveries and degree of the bladder neck prolapsus. Results: Significant differences were found in the thickness of each three layers of the urethra between the two groups (P < .05). There was a significantly higher pubourethral ligament distortion (P = .024) and larger vesicourethral angle (P = .000) in women with SUI. In women with SUI, there was no significant relationship between the number of deliveries and the degree of the bladder neck prolapsus (P > .05). Conclusion: The combined usage of the EV-MRI and DP-MRI can provide complementary information concerning certain structural abnormalities with specific dysfunction, such as vesicourethral angle increase and pubourethral ligament distortion in patients with SUI.